Muscle fibre adaptations, strength and power development during strength and/or endurance training in 40 to 65-yr-old women - Arija Blázquez, Alfredo (2007)
The purpose of the present study was to examine muscle fibre composition and fibre size adaptations following 6 months of resistance and endurance training in 40 to 65-yr-old women (mean age 52 ±7 yr), and the changes in neuromuscular performance. The experimental groups were composed of strength training (S) group (n =27), endurance training (E) group (n = 27), concurrent S and E (C) group (n = 25) and control group (n = 20).